Chemical constituents from cratoxylum cochinchnense and cratoxylum formossum ssp. pruniflorum and their biological activities - Nawong Boonnak (Prince of Songkla University, 2021)
Thesis (Ph.D., Organic Chemistry)--Prince of Songkla University, 2011